2020
DOI: 10.2196/23366
|View full text |Cite
|
Sign up to set email alerts
|

Plausibility of Using a Checklist With YouTube to Facilitate the Discovery of Acute Low Back Pain Self-Management Content: Exploratory Study

Abstract: Background Access to guideline-consistent effective care for acute low back pain (ALBP) is generally regarded as limited. Researchers have recognized the potential of YouTube as a clinical and patient education resource that may improve access to appropriate care. However, the heterogeneity of evaluation approaches and variable quality of health information have generally limited the potential of YouTube as a self-management intervention. Objective This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…Khazaal et al [ 34 ] developed an abbreviated 6-item version (Brief DISCERN) with comparable reliability and validity, which preserves the advantages of the original tool while affording a potentially more user-friendly format. Thus, we used the Brief DISCERN quality assessment tool, which has been previously used [ 35 , 36 ]. Sources are scored from 1 to 5 based on the criteria listed in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Khazaal et al [ 34 ] developed an abbreviated 6-item version (Brief DISCERN) with comparable reliability and validity, which preserves the advantages of the original tool while affording a potentially more user-friendly format. Thus, we used the Brief DISCERN quality assessment tool, which has been previously used [ 35 , 36 ]. Sources are scored from 1 to 5 based on the criteria listed in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…We modified the methods developed by Zheluk and Maddock for their analysis of YouTube videos about acute non-specific low back pain (ALBP) [ 31 ]. First, in this study, we have assumed that ANSBP TikTok videos are viewed by patients for self-care guidance only (i.e., TikTok videos are viewed independent of health advice).…”
Section: Methodsmentioning
confidence: 99%
“…Third, in this project, we did not analyse information quality. Zheluk and Maddock found that the Brief DISCERN information quality instrument was less sensitive in identifying differences in the self-management content of YouTube videos than an evidence-based reference list [ 31 ]. Similarly, Azer and colleagues suggested that information quality tools were not suitable for analysis of YouTube video content [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations